Metallic perforated plate lattices with superior buckling strength - Lei Zhang; Mingpei Cang; Junhao Ding; Winston Wai Shing Ma; Xiangyang Zhu; Yang Lu; Xu Song; Huachen Cui; Michael Yu Wang (Materials & Design)
Plate lattices possess promising stiffness and yielding strength; however, their closed-cell topology dramatically increases the manufacturing difficulty. While introducing micro holes can effectively improve the manufacturability, design rationale to minimize the strength reduction induced by micro holes remain elusive. In particular, low-density plate lattices are prone to buckling failure, and design optimization for buckling strength is of great importance. Here, we propose a design method for low-density perforated plate lattices to achieve superior buckling strength using a Rayleigh quotient based theoretical criteria to determine the optimized locations of micro holes. Through linear buckling and post-buckling analysis, we demonstrate that introducing micro holes at the proposed locations can increase the critical buckling stresses and maintain the post-buckling compressive strength compared with the unperforated plate lattices. Three representative perforated plate lattices with the relative density range of 5.6%∼37.1% were fabricated with micro laser powder bed fusion process. Compression testing results show that the proposed perforated plate lattices exhibit superior Young’s modulus and compressive strength over shell and truss lattices in the considered relative density range.